Soil Test Phosphorus Recovery from Livestock Manures Compared with Inorganic Fertilizer in Soil Incubations - J. Craig Miller; T. Astatkie; Ali Madani (Applied and Environmental Soil Science)
This paper compared dairy and hen manure P recovery relative to fertilizer P recovery for two Nova Scotia soils with different antecedent soil test P (STP), incubated for 5, 15, 30, 60, and 110 days. Fertilizer equivalence of manure P was expressed as P recovery ratio in percentage points (%PRR). Repeated measures analysis with soil pH covariate revealed: (1) manure %PRR averaged 72% (low-STP soil) and 80% (medium-STP soil), (2) there were no significant differences in %PRR between dairy and hen manure, and (3) manure %PRR decreased with incubation time for the low-STP soil but not for the medium-STP soil. The soil pH covariate was significant for both low- and medium-STP soils, and the relationship with %PRR was positive for low- but not for the medium-STP soil.